KAJIAN YURIDIS KESESUAIAN PERMOHONAN PKPU TERHADAP PASAL 222 UU NOMOR 37 TAHUN 2004 - Najwa Fitria Mulyasari; Ismawati Septiningsih (Sebelas Maret University, 2025)
This article examines the PKPU Application submitted by PT Bank QNB Indonesia Tbk against PT Senang Kharisma Textil and Iwan Setiawan Lukminto in light of Article 222 of Law Number 37 of 2004. The type of research used by the author in this article is normative legal research with a prescriptive nature, where this research uses a case study approach with legal material from literary studies and analyzed through deductive syllogism. The purpose of this article is to determine the suitability of the PKPU Application submitted by PT Bank QNB Indonesia Tbk with the requirements for submitting a PKPU as stated in Article 222 of Law Number 37 of 2004. The findings show that there is a mismatch between the requirements for submitting a PKPU Application as stated in Article 222 creditor the PKPU Application submitted by PT Bank QNB Indonesia Tbk against PT Senang Kharisma Textil and Iwan Setiawan Lukminto, specifically creditor on the requirement that there be more than one creditors and submitted when the debt is due and can be collected.